Patient-centered care for people with depression and anxiety: an integrative review protocol - Pinho, Lara Guedes de (2021)
Introduction: Depression and anxiety are mental diseases found worldwide, with the tendency to worsen in the current pandemic period. These illnesses contribute the most to the world’s rate of years lived with disability. We aim to identify and synthesize indicators for the care process of the person with depression and/or anxiety disorders, based on patient-centered care, going through the stages of diagnostic assessment, care planning, and intervention. Methods and analysis: An integrative literature review will be conducted, and the research carried out on the following databases: MEDLINE, PsycINFO, Scopus, and Psychology and Behavioral Sciences Collection, CINAHL, Web of Science, TrialRegistry, and MedicLatina. The research strategy contains the following terms MesH or similar: “patient-centered care”, “depression”, and “anxiety”. Two independent revisers will perform the inclusion and exclusion criteria analysis, the quality analysis of the data, and its extraction for synthesis. Disagreements will be resolved by a third revisor. All studies related to diagnostic assessment, care planning, or intervention strategies will be included as long as they focus on care focused on people with depression and anxiety, regardless of the context. Given the plurality of the eligible studies, we used the narrative synthesis method for the analysis of the diagnostic assessment, the care and intervention planning, and the facilitators and barriers.